﻿Antibacterial activity of Medan Butterfly pea (Clitoria ternatea L.) corolla extract against Streptococcus mutans ATCC®25175™ and Staphylococcus aureus ATCC®6538™ - Denny Satria; Ervina Sofyanti; Pitu Wulandari; Fajarini; Sri Dewi Pakpahan; Stephanie Artha Limbong (Pensoft Publishers, 2022)
Streptococcus mutans (S. mutans) and Staphylococcus aureus (S. aureus) pathogenicity that alter biofim, has become one of risk factor in orthodontic treatment. The medicinal plant's Butterfly pea efficacy as an antibacterial agent should be confirmed in dentistry. The purpose of this study is to investigate the antibacterial activity of Medan butterfly pea corolla extract (BPCE) against S. mutans ATCC®25175™ and S. aureus ATCC®6538™. This is a laboratory experiment with Post Test Only Group Design. The minimum inhibitory concentration of BPCE is 6.25 mg/mL. The best concentration of butterfly pea extract to inhibit biofilm formation (antibiofilm) is 100 mg/mL. There was a significant difference (p < 0.05) for antibiofilm activity assays and determination of intramembrane cellular leakage. Although Medan BPCE was inadequate enough in forming antibiofilm and caused intramembrane leakage of S. mutans and S. aureus, further studies in exploring the potential morphological traits of these herbs related to orthodontic products are quite promising.